Thermal effect on stability and minimum oil film thickness of a deep/shallow pockets conical bearing. Issue 10 (18th June 2020) - Wu, Ningning; Guo, Hong; Yang, Shuai; Zhang, Shaolin
Abstract : Purpose: This paper aims to study the influence of thermal effect on the performance for a high-speed conical hybrid bearing including stability and minimum oil film thickness. Design/methodology/approach: A thermal hydrodynamic (THD) model and dynamic model of single mass rigid rotor system were established by taking conical hybrid bearing with shallow and deep pockets as the research object, dynamic coefficient and stability parameters of bearing-rotor system were obtained by using finite element method (FEM) and finite difference method (FDM) to solve computational models of Reynolds equation, energy equation and viscosity-temperature equation. Minimum oil film thickness was obtained based on bearing force balance. Dynamic coefficient was compared with previous findings. Findings: After considering thermal effect, the dimensionless critical mass decreases, a significant decrease in the instability speed, and the stability of the system decreases greatly; the minimum oil film thickness decreases because of thermal effect. Originality/value: The thermal effect is combined with dynamic characteristics to analyze stability of the rotor system for a conical hybrid bearing. Influence of thermal effect on minimum oil film thickness is studied. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-12-2019-0542/